EZH2 is highly expressed in pituitary adenomas and associated with proliferation - Schult, David; Hoelsken, Annett; Siegel, Sonja; Buchfelder, Michael; Fahlbusch, Rudolf; Kreitschmann-Andermahr, Ilonka; Buslei, Rolf (Scientific Reports, 2015)
Enhancer of zeste homolog 2 (EZH2) is a core epigenetic regulator, playing a crucial role in cell cycle regulation. The protein is known to be associated with proliferation and worse outcome in several tumor entities. In this study, we immunohistochemically investigated the expression pattern of EZH2 in a large cohort of pituitary tumors. These results were correlated with clinical features and double immunofluorescence stainings (DIS) were conducted to evaluate co-expression of EZH2 and proliferation marker Ki-67. Furthermore, we analyzed the effect of EZH2 inhibition on cell proliferation in vitro using the pituitary cell line AtT-20. While in the normal anterior pituitary EZH2 was almost absent, the cohort of tumors showed enhanced expression levels (p <= 0.0005). This was positively associated with Ki-67 indices (r = 0.834, p <= 0.0005) and DIF confirmed a predominant co-expression of both markers. In vitro experiments revealed a significant (p <= 0.05) decrease of tumor cell proliferation using the EZH2 inhibitor GSK126. Our results further support that epigenetic events are involved in the pathogenesis and biology of pituitary adenomas (PA). Therefore, EZH2 may function as a new potential target for therapeutic interventions in PA.
EVALuna2:7303